The Encounter between Indigenous Religions, World Religions and Modernity - Syamsul Maarif (Universitas Islam Negeri Alauddin Makassar, 2012)
This paper discusses how Ammatoans, an indigenous people of Sulawesi, embrace Islam, adjust their life with modernity, and at the same time preserve their indigenous religion. It specifically talks about the practice of Ramadan through which those three elements are articulated by Ammatoans. Building insight on Stuart Hall’s theory of “articulation,” this paper argues that those three elements are contextually exercised, advocated, challenged, and questioned, and even “humiliated” by Ammatoans. It shows that Ammatoans, with their own ways, exercise Islam and modernity as much as their indigenous religion. The three elements, for Ammatoans, are not mutually exclusive. They are dialectical as they are practiced by Ammatoans.